Non-neuronal cholinergic system in the heart influences its homeostasis and an extra-cardiac site, the blood-brain barrier - Kakinuma, Yoshihiko (Frontiers in Cardiovascular Medicine, 2024)
The non-neuronal cholinergic system of the cardiovascular system has recently gained attention because of its origin. The final product of this system is acetylcholine (ACh) not derived from the parasympathetic nervous system but from cardiomyocytes, endothelial cells, and immune cells. Accordingly, it is defined as an ACh synthesis system by non-neuronal cells. This system plays a dispensable role in the heart and cardiomyocytes, which is confirmed by pharmacological and genetic studies using murine models, such as models with the deletion of vesicular ACh transporter gene and modulation of the choline acetyltransferase (ChAT) gene. In these models, this system sustained the physiological function of the heart, prevented the development of cardiac hypertrophy, and negatively regulated the cardiac metabolism and reactive oxygen species production, resulting in sustained cardiac homeostasis. Further, it regulated extra-cardiac organs, as revealed by heartspecific ChAT transgenic (hChAT tg) mice. They showed enhanced functions of the blood-brain barrier (BBB), indicating that the augmented system influences the BBB through the vagus nerve. Therefore, the non-neuronal cardiac cholinergic system indirectly influences brain function. This mini-review summarizes the critical cardiac phenotypes of hChAT tg mice and focuses on the effect of the system on BBB functions. We discuss the possibility that a cholinergic signal or vagus nerve influences the expression of BBB component proteins to consolidate the barrier, leading to the downregulation of inflammatory responses in the brain, and the modulation of cardiac dysfunctionrelated effects on the brain. This also discusses the possible interventions using the non-neuronal cardiac cholinergic system.